Penerapan Pidana Pengganti Dalam Pembayaran Restitusi Terhadap Anak Korban Tindak Pidana Kekerasan Seksual - Diana, Anisa Roshda; Maryano, Maryano; Chandra, Tofik Yanuar (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
In Perma Number 1 of 2022 concerning Procedures for Settlement of Applications and Granting of Restitution and Compensation to Victims of Criminal Acts, the concept of substitute punishment has actually been accommodated by providing space by regulating it partially. In addition, seen from the perspective of systematic interpretation and interdisciplinary interpretation, there are several laws that regulate substitute punishment for restitution, one of which is the provision of Article 33 paragraph (7) of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. However, in practice, perpetrators of criminal acts who are required to pay restitution based on a court decision that has permanent legal force, state that they refuse to pay restitution on the grounds that they cannot afford it so that they serve a subsidiary sentence because they do not pay restitution. Then the problem is that the subsidiary sentence that they must undergo is often not commensurate with the actions or the value of the restitution that must be paid, so that perpetrators of criminal acts prefer to serve a substitute sentence rather than pay restitution. Methods used in this study This study uses descriptive analytical research, which is carried out with the main aim of providing an objective picture or description of a situation. With the statute approach, case approach, conceptual approach, analytical approach. The results of the study recommend that in the form of efforts to ensure the fulfillment of the rights of victims of sexual violence in the form of restitution, there needs to be rules or guidelines for judges in deciding on substitute (subsidiary) punishment for restitution, so that the judge's decision has coercive power and has uniformity. From the perspective of the victim, restitution is used to restore the victim's condition to the state before the crime occurred. Meanwhile, from the perpetrator's side, payment of restitution is a form of accountability for the occurrence of the crime. Although restitution is a form of accountability for the perpetrator, there are no rules or guidelines that confirm/regulate the provision of substitute (subsidiary) punishment if restitution is not paid by the perpetrator to the victim